2012
DOI: 10.2151/sola.2012-036
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons between XCH<sub>4</sub> from GOSAT Shortwave and Thermal Infrared Spectra and Aircraft CH<sub>4</sub> Measurements over Guam

Abstract: The Thermal and Near-infrared Sensor for Carbon Observation Fourier Transform Spectrometer (TANSO-FTS) on board the Greenhouse Gases Observing Satellite (GOSAT) simultaneously observes column abundances and profiles of CH 4 in the same field of view, from the shortwave infrared (SWIR) and thermal infrared (TIR) bands, respectively. We compared CH 4 column-averaged dry-air mole fractions (XCH 4 ) derived from the SWIR band, XCH 4 calculated from the TIR CH 4 profiles, and XCH 4 calculated from the CH 4 data obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 26 publications
0
38
0
Order By: Relevance
“…In this study, we followed a method similar to Saitoh et al (2012). For the altitudes between 0.5 and 7.0 km (about 400 hPa), aircraft measurements are available.…”
Section: Analysis Methods -Xch 4 Estimation From Aircraft Data -mentioning
confidence: 99%
“…In this study, we followed a method similar to Saitoh et al (2012). For the altitudes between 0.5 and 7.0 km (about 400 hPa), aircraft measurements are available.…”
Section: Analysis Methods -Xch 4 Estimation From Aircraft Data -mentioning
confidence: 99%
“…TANSO-FTS consists of three bands in the SWIR region and one band in the TIR region. Column amounts of greenhouse gases are observed in the SWIR bands, and vertical information of gas concentrations are obtained in the TIR band (Yoshida et al, 2011Saitoh et al, 2009Saitoh et al, , 2012Ohyama et al, 2012Ohyama et al, , 2013. Kuze et al (2012) provided a detailed description of the methods used for the processing and calibration of level 1B (L1B) spectral data from TANSO-FTS.…”
Section: Gosat Observationsmentioning
confidence: 99%
“…Column-averaged dry air mole fractions of CO 2 (XCO 2 ) and CH 4 (XCH 4 ) are retrieved from the Short-Wavelength InfraRed (SWIR) spectra of the Thermal And Near-infrared Sensor for carbon Observation -Fourier Transform Spectrometer (TANSO-FTS) onboard GOSAT. Validation of XCO 2 and XCH 4 derived from the GOSAT TANSO-FTS has been conducted by using ground-based high-resolution Fourier Transform Spectrometer (ground-based FTS) data and aircraft measurements Saitoh et al, 2012;Yoshida et al, 2013;Inoue et al, 2013Inoue et al, , 2014Gavrilov et al, 2014). The results showed that the GOSAT SWIR XCO 2 measurements (Ver.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements in the SWIR and thermal infrared (TIR) bands of TANSO-FTS allow the retrievals over cloud-free regions of XCO 2 and XCH 4 , and CO 2 and CH 4 profiles, respectively. Saitoh et al, 2012). More recently, Kuze et al (2016) reported update on the performance of GOSAT TANSO-FTS sensor and important changes to the data product which has been made available to users.…”
Section: Introductionmentioning
confidence: 99%